Utilizing The Edmodo Application As A Learning Media In SD Alwasliyah 26 Medan - khairul ummi; Edy Victor Haryanto; Ivy Lazuli; Juli Iriani; Bob Subhan Riza; Noprita Elisabeth S (JUDIMAS, 2020)
The use of e-learning in learning is very much needed in this century. The use of learning media in SD Alwasliyah 26 Medan is very less varied. Due to the lack of knowledge about technology and information as well as the use and use of the internet for teachers at SD Alwasliyah 26 Medan. The purpose of implementing this community service activity is to provide an understanding of the varied learning media, namely Edmodo, to increase the skills of teaching teachers to support teacher performance in utilizing technology in the school. The method used is to carry out direct practice by holding training by making Edmodo learning media guided by presenters from the community service implementation team so that the process is known from start to finish. The object of this activity is the teachers of SD Alwasliyah 26 Medan